The impact of COVID-19 vaccination on long-term risk of new-onset atrial fibrillation/flutter after COVID-19 infection: A retrospective cohort study - Ching-Chung Ko; Jheng-Yan Wu; Kuo-Chuan Hung; Shu-Wei Liao; Ya-Wen Tsai; Tsung Yu; Chien-Ming Lin; I-Wen Chen (PLoS ONE, 2026)
Purpose COVID-19 infection has been associated with cardiovascular complications, including new-onset atrial fibrillation/flutter (NOAF). However, the potential protective effect of COVID-19 vaccination against long-term NOAF risk following COVID-19 infection remains unclear. Methods This retrospective cohort study used the TriNetX Research Network to identify adults diagnosed with COVID-19. Patients were divided into a vaccine group and control group (unvaccinated). After propensity score matching (238,750 patients per group), we assessed the primary outcome of 24-month NOAF incidence, with secondary outcomes at 1, 6 and 12 months. Subgroup analyses examined effects across patient characteristics and comorbidities. Sensitivity analysis was performed by excluding patients with severe COVID-19 illness. Results The 24-month NOAF incidence was significantly lower in the vaccine group compared to the control group (1.91% vs 2.18%; HR: 0.82, 95% CI: 0.78–0.85). This protective effect was also observed at 1 month (HR: 0.73, p < 0.001), 6 months (HR: 0.71, p < 0.001), and 12 months (HR: 0.77, p < 0.001). Sensitivity analysis confirmed these findings (HR: 0.79 at 24 months). Subgroup analyses demonstrated that COVID-19 vaccination provided significant protection against NOAF across all examined subgroups, with younger patients (18–60 years) showing greater risk reduction compared to older individuals. Conclusion COVID-19 vaccination was associated with a significantly reduced 24-month risk of NOAF after COVID-19 infection. These findings suggest vaccination may mitigate long-term cardiovascular sequelae of COVID-19. Future research should elucidate underlying protective mechanisms and optimize vaccination strategies for cardiovascular protection, particularly in high-risk populations.